2008
DOI: 10.1016/j.abb.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of retinoid synthesis from β-carotene

Abstract: Retinoids are indispensable for the health of mammals, which cannot synthesize retinoids de novo. Retinoids are derived from dietary provitamin A carotenoids, like β-carotene, through the actions β-carotene 15,15′ monooxygenase (BCMO1). As the substrates for retinoid metabolizing enzymes are water insoluble, they must be transported intracellularly bound to cellular retinol-binding proteins. Our studies suggest that cellular retinol binding protein, type I (RBP1) acts as an intracellular sensor of retinoid sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…Fierce et al [18] argued that BCMO1 is not essential for maintaining vitamin A stores due to their observation that liver vitamin A stores were not different between BCMO1 -/-and WT animals. However, it is likely that this discrepancy is caused by high hepatic retinoid concentrations at the beginning of the study by [18] since (a) WT and BCMO1 -/-breeders were not subjected to a diet depleted of vitamin A, and (b) the duration of the b-carotene/low vitamin A feeding period was shorter than in the study from [29]. Indeed, it has been shown that it is very difficult to trigger vitamin A deficiency in mice after weaning [53].…”
Section: Carotenoid Oxygenasesmentioning
confidence: 99%
“…Fierce et al [18] argued that BCMO1 is not essential for maintaining vitamin A stores due to their observation that liver vitamin A stores were not different between BCMO1 -/-and WT animals. However, it is likely that this discrepancy is caused by high hepatic retinoid concentrations at the beginning of the study by [18] since (a) WT and BCMO1 -/-breeders were not subjected to a diet depleted of vitamin A, and (b) the duration of the b-carotene/low vitamin A feeding period was shorter than in the study from [29]. Indeed, it has been shown that it is very difficult to trigger vitamin A deficiency in mice after weaning [53].…”
Section: Carotenoid Oxygenasesmentioning
confidence: 99%
“…For all of our experiments, we used male WT C57BL/6J mice (Jackson Laboratory) and Bco1 Ϫ/Ϫ mice congenic in the C57BL/6J genetic background. Bco1 Ϫ/Ϫ mice, which were originally described for the mixed C57BL/6;129svJ genetic background (14), have undergone 10 backcrosses with C57BL/6J mice to render them congenic in this inbred background. Genotypes of Bco1 Ϫ/Ϫ mice were determined by PCR using a previously described protocol (14).…”
Section: Methodsmentioning
confidence: 99%
“…An open reading frame was subcloned into a pET28 bacterial expression vector containing a 3Ј histidine tag, and the resulting sequence was verified through DNA sequencing (University of Washington DNA sequencing facility). Expression of the enzyme was induced with 1 mM isopropyl 1-thio-␤-D-galactopyranoside, and purification was performed using His⅐Bind resin (Novagen, San Diego, CA) as described previously (16). Purified enzyme was dialyzed against 20 mM Hepes buffer (pH 8.5) containing 150 mM KCl and 1 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…Retinol and Retinyl Ester Analysis-Retinoid extractions and detections were carried out as described previously (16,22 Retinoic Acid Analysis from Testes-Intratesticular retinoic acid (RA) concentrations were measured by LC-MS/MS as described previously with a few modifications to the sample preparation (23). All sample processing, preparation, and extraction were conducted on ice under red light to minimize degradation of retinoic acids.…”
Section: Methodsmentioning
confidence: 99%